RETRACTED: A detailed thermohydraulic performance assessment of surface-modified silver nanofluids in turbulent convective heat transfer (Retracted article. See vol. 151, pg. 1919, 2026) - Bunpheng, Wasurat; Dhairiyasamy, Ratchagaraja; Almuflih, Ali Saeed; Alam, Mohammad Mukhtar; Dixit, Saurav; Agbulut, Umit (SPRINGER, 2024)
This study investigates the thermohydraulic performance of surface-modified silver nanofluids in turbulent convective heat transfer applications. The primary objective is to evaluate the impact of citrate, lipoic acid, and silica surface modifications on heat transfer coefficients, pressure drops, and friction factors under turbulent flow conditions. Silver nanoparticles (50 nm) with the specified surface modifications were synthesized and dispersed in deionized water, ensuring stable nanofluid preparations. Experimental evaluations were conducted in a smooth brass tube with a uniform heat flux, covering Reynolds numbers from 3400 to 21,800, mass flow rates of 32 to 78 g s-1, and inlet temperatures of 26 degrees C, 31 degrees C, and 36 degrees C. Key findings indicate that the silica-shelled nanofluid (Ag/S) exhibited a significant 35% increase in the heat transfer coefficient compared to DI water, while citrate-coated (Ag/C) and lipoic acid-coated (Ag/L) nanofluids showed slight decreases of 0.2% and 2%, respectively. The mean Nusselt number for Ag/S also increased by 9%, demonstrating enhanced heat transfer capabilities. Surface-modified nanofluids experienced higher pressure drops and friction factors than the base fluid. Ag/C showed a 7.7% increase in pressure drop, Ag/L a 12.3% increase, and Ag/S a 12.5% increase, correlating with an 11.9% rise in viscosity. While surface-modified silver nanofluids, particularly silica-shelled, can significantly improve heat transfer performance, the associated increases in pressure drops and friction factors must be carefully balanced for specific applications. Future research should explore long-term stability, varying nanoparticle concentrations, and more complex geometries to optimize nanofluid formulations for targeted heat transfer applications.
Keywords: Nanofluids; Silver nanoparticles; Surface modification; Turbulent convective heat transfer; Energy efficiency; NANOPARTICLES; TUBE; Thermodynamics; Chemistry